Signature of miRNAs derived from the circulating exosomes of patients with amyotrophic lateral sclerosis - Cheng, Yang-Fan; Gu, Xiao-Jing; Yang, Tian-Mi; Wei, Qian-Qian; Cao, Bei; Zhang, Yang; Shang, Hui-Fang; Chen, Yong-Ping (Frontiers in Aging Neuroscience, 2023)
Background: Amyotrophic lateral sclerosis (ALS) is a progressive, fatal neurodegenerative disorder with an unclear pathophysiology and few therapeutic options. Mutations in SOD1 and C9orf72 are most common in Asian and Caucasian patients with ALS, respectively. Aberrant miRNAs found in patients with gene-mutated ALS may be involved in the pathogenesis of gene-specific ALS and sporadic ALS (SALS). The aim of this study was to screen for differentially expressed miRNAs from exosomes in patients with ALS and healthy controls (HCs), and to construct a miRNA-based diagnostic model to classify patients and HCs. Methods: We compared circulating exosomes-derived miRNAs of ALS patients and HCs using two cohorts; a discovery cohort (three SOD1- mutated ALS, three C9orf72- mutated ALS patients, and three HCs) analyzed by microarray and a validation cohort (16 gene- mutated ALS patients, 65 SALS patients, and 61 HCs) confirmed by RT-qPCR. The support vector machine (SVM) model was used to help diagnose ALS using 5 differentially expressed miRNAs between SALS and HCs. Results: A total of 64 differentially expressed miRNAs in SOD1-mutated ALS and 128 dysregulated miRNAs in C9orf72-mutated ALS patients were obtained by microarray compared to HCs. Of these, 11 overlapping dysregulated miRNAs were identified in both groups. Among 14 top hit candidate miRNAs validated by RT-qPCR, hsa-miR-34a-3p was specifically downregulated in SOD1-mutated ALS patients, while hsa-miR-1306-3p was downregulated in ALS patients with both SOD1 and C9orf72 mutations. In addition, hsa-miR-199a-3p and hsa-miR-30b-5p were upregulated significantly in SALS patients, while hsa-miR-501-3p, hsa-miR-103a-2-5p, and hsa-miR-181d-5p had a trend to be upregulated. The SVM diagnostic model used five miRNAs as features to distinguish ALS from HCs in our cohort with an AUC of 0.80. Conclusions: Our study identified aberrant miRNAs from exosomes of SALS and ALS patients with SOD1/C9orf72 mutations, and provided additional evidence that aberrant miRNAs were involved in the pathogenesis of ALS regardless of the presence or absence of the gene mutation. The machine learning algorithm had high accuracy in predicting the diagnosis of ALS, shedding light on the foundation for the clinical application of blood tests in the diagnosis of ALS and revealing the pathological mechanisms of the disease.